Creation of a Professionalism Scale for Hospitality Students: An Exploratory Study. (18th November 2014) - Kaufman, Tammie J.; Ricci, Peter
The hospitality industry is dependent on a professional staff to exceed guests' expectations. Existing research has focused primarily on the various attributes necessary for success in the hospitality industry. The primary focus of this research was professionalism and hospitality students' self-perception of their professional attributes. Data collected from a focus group of hospitality human resource managers were used to develop a professionalism scale. The scale produced five factors that explained 53.6% of the variance in the responses. Students were more likely to agree in their preparedness for the interview process, but less in agreement of their preparedness for workplace issues. This research provides an exploratory study into a student's perception of his or her own professional abilities and could be used as a placement tool for human resource managers and a benchmark to determine student's professional aptitude by hospitality management professors.